(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
In recent decades, the pedagogical realm in Uzbekistan has witnessed an intensified focus on foreign language education, underlined by the adoption of the National Program for Personnel Training and subsequent directives that foster an environment conducive to language teaching methodologies. As societies evolve, contemporary pedagogical science is tasked with cultivating individuals who aspire for maximal self-realization, are receptive to novel experiences, and possess the capacity for deliberate decision-making in diverse life scenarios. Achieving this necessitates imparting students with communicative competence encompassing speech, linguistic, and sociolinguistic skills. The ultimate educational outcome aims to shape students into "linguistic personalities". Current pedagogical advancements advocate for innovative methods, particularly in teaching Russian as a foreign language. Such methods range from cluster techniques and diary-keeping to the implementation of TIPS (Theory of Inventive Problem Solving) elements and project-based learning. Employing these avant-garde techniques not only heightens student engagement and creativity but also fosters critical thinking, communicative skills, and an adeptness in handling vast information. Additionally, group-based learning technologies, especially when integrated with native Russian speakers, are instrumental in enhancing the communicative competence of students. Comparative linguistic analyses of text materials in both Russian and native languages, especially in areas of lexicon, phonetics, morphology, and stylistics, have proven to be especially effective. This synthesis underscores the indispensable role of innovative methodologies in optimizing the teaching and learning of Russian as a foreign language in Uzbekistan’s higher education institutions.